علاقة الظروف المناخية بالأنشطة الإنسانية في منطقة وادي سوف - مليك، توفيق الجباري. شيبة، حياة (جامعة الوادي university of Eloued, 2017)
Summary The climatic conditions have a great impact on the human life and the practice of various activities, considering that the climate is all the phenomena that are related to the state of weather such as wind, heat and rain. In this study the researcher tried to address the prevailing climatic conditions in Oued Souf region, and focused on the indices of heat, wind and the research of their relation with exercising Social, cultural, and agricultural activities, and how the individual deals with the harsh weather conditions known of the region, especially the summer which is known for its extreme heat, and the spring season, where the wind is frequent. The purpose of this study is to highlight whether the climatic conditions are related to the human activities in the region of Oued Souf and to clarify the general lifestyle by addressing to the most important activities practiced by the residents of the region and trying to highlight the methods and ideas that they developed to adapt with the desert environment. The methodology of this study is the ethnographic and the descriptive approach as they are appropriate methods to deal with this subject by taking a sample from the original society and focus the work on it. The sample is of 30 individuals of 45 years. The used tools in this study is the interview and simple observation, where the achieved results are:  The indexes of heat and wind are related to human activity. They determine the population lifestyle in Oued souf. The residents of the region continue to try to adapt and coexist with the climate by using all the possible efforts and thought until the region reached what it is today after it was a desert where there was almost no life.
مذكرة ماستر علوم اجتماعية تخصص علم اجتماع البيئة
Keywords: النشاط الإنساني، المناخ; Activité humaine, climat; Human activity, climate